Synthesis through 3D printing : formation of 3D coordination polymers - Halevi, Oded (2021)
Coordination polymers (CPs) and coordination network solids such as metal–organic frameworks (MOFs) have gained increasing interest during recent years due to their unique properties and potential applications. Preparing 3D printed structures using CP would provide many advantages towards utilization in fields such as catalysis and sensing. So far, functional 3D structures were printed mostly by dispersing pre-synthesized particles of CPs and MOFs within a polymerizable carrier. This resulted in a CP active material dispersed within a 3D polymeric object, which may obstruct or impede the intrinsic properties of the CP. Here, we present a new concept for obtaining 3D free-standing objects solely composed of CP material, starting from coordination metal complexes as the monomeric building blocks, and utilizing the 3D printer itself as a tool to in situ synthesize a coordination polymer during printing, and to shape it into a 3D object, simultaneously. To demonstrate this, a 3D-shaped nickel tetra-acrylamide monomeric complex composed solely of the CP without a binder was successfully prepared using our direct print-and-form approach. We expect that this work will open new directions and unlimited potential in additive manufacturing and utilization of CPs.